A educação no contexto da crise do capital: uma análise a partir da ideia de discurso em Jacques Lacan - Lima, Hipácia Rocha (2022)
This research aims to study aspects of the notion of capitalist discourse, according to Jacques Lacan, in order to identify how such discourse comes to influence pedagogical praxis and current education. Our intention, in this way, goes through an investigation that seeks to know how the capitalist ideology was constituted in the dominant discourse, by weaving social behaviors and educational processes in the molds of the political and economic organizations of neoliberalism. At this point, the problem also touches on an angle that affects the subject, under a type of suffering in the order of a social or psychic symptom, while certain structures dominate the subject's practices through social ties in the discourses. The study is justified given the need to research the consequences of neoliberal policy in education, to think about the alienating structure established by capital, the loss of emancipatory activities in education and the retreat to reflective practices of the act of educating. It is thus considered that the effects of market demands are already acting on the values of the school's training projects, when the interest in the production of human capital induces a framework of pressure for school success, in the suffering and psychological illness of young people and in the objectification of children in quantitative data. This perspective will be worked through the reading of Lacan's work The reverse of psychoanalysis (1969-1970), in order to highlight the capitalist discourse in the social mediation of language through the subject's schedules and in the incorporation of institutional relations of current education.